Decision Support System For Teacher Performance Assessment at the Yayasan Pendidikan Islam Al-Islamiyah with the Analytical Hierarchy Process Method (AHP) - Sulhi Romadhoni; Anita Diana (Universitas Negeri Medan, 2022)
This study focuses on the development of a decision support system (DSS) for teacher performance assessment at the Al-Islamiyah Islamic Education Foundation. In an educational institution, schools have teachers who are assets that must be owned by schools in creating a quality education process. The problem that occurs at this foundation is that there is no proper method and application of the teacher performance appraisal system, and also the large number of teachers, so it is difficult to choose the best teacher. Therefore, appropriate methods and DSS are needed to overcome the existing obstacles. The Analytical Hierarchy Process (AHP) method is one method that can be used in determining the best teacher performance assessment in determining the selection of the best teacher. The criteria that have been set are based on presence, neatness of dress, discipline, teaching ability, and responsibility. This study aims to determine the right method and build a DSS for assessing teacher performance at the Al-Islamiyah Islamic Education Foundation school in determining the best teacher. This DSS produces an alternative priority order, which can be used as a problem-solving tool in determining teacher performance appraisals and selecting the best teacher.